A new concept to achieve optimal weight gain in malnourished infants on total parenteral nutrition - Abi Nader, Elie (2017)
Background Infants with intestinal failure (IF) are at increased risk of malnutrition and require adapted nutrition support. Optimal weight gain during nutrition rehabilitation should occur at the velocity of statural age (adjusted to the 50th percentile of height) and not chronological age. The aim of this study was to assess the relationship between weight gain during catch‐up growth, nonprotein energy intake (NPEI) provided by total parenteral nutrition (TPN), and resting energy expenditure (REE) in children with severe malnutrition due to IF. Materials and Methods This retrospective study included all infants with severe malnutrition treated with TPN for IF between January 1, 2010, and December 31, 2013. They all had no or minimal oral intake (<10% REE). The REE was calculated using the Schofield equations. Results Seventeen children were included (11 boys) with a mean age at TPN onset of 5 mo. They were followed for a mean duration of 39 days. On admission, body weight and height were –3.1 ± 0.9 and –3.3 ± 1.3 SD, respectively. The indications for TPN were short bowel syndrome (n = 10), congenital enteropathy (microvillous inclusion disease, n = 6) and chronic intestinal pseudo‐obstruction syndrome (n = 1). After 28 days of nutrition rehabilitation with full NPEI from TPN, the observed weight gain was 110 ± 5% of optimal weight gain for statural age. The mean NPEI from TPN was 104.3 ± 8.0 kcal/kg/d. The mean ratio of NPEI over REE was 2.1 ± 0.2. Conclusion Optimal weight gain was achieved with NPEI from TPN twice the REE in severely malnourished infants with IF. NPEI values were adequate and not excessive for age.